Predictors of treatment response for cognitive behaviour therapy for prolonged grief disorder. (29th December 2017) - Bryant, Richard A.; Kenny, Lucy; Joscelyne, Amy; Rawson, Natasha; Maccallum, Fiona; Cahill, Catherine; Hopwood, Sally
ABSTRACT: Background : Prolonged grief disorder (PGD) causes significant impairment in approximately 7% of bereaved people. Although cognitive behaviour therapy (CBT) has been shown to effectively treat PGD, there is a need to identify predictors of treatment non-response. Methods : PGD patients ( N = 80) were randomly allocated to receive 10 weekly two-hour group CBT sessions and (a) four individual sessions of exposure therapy or (b) CBT without exposure. PGD was assessed by self-report measures at baseline, post-treatment ( N = 61), and six-months ( N = 56) after treatment. Results : Post-treatment assessments indicated that greater reduction in grief severity relative to pretreatment levels was associated with being in the CBT/Exposure condition, and lower baseline levels of self-blame and avoidance. At follow-up, greater grief symptom reduction was associated with being in the CBT/Exposure condition and lower levels of avoidance. Conclusions : These patterns suggest that strategies that target excessive self-blame and avoidance during treatment may enhance response to grief-focused cognitive behaviour therapy.